A Plasma 5-Marker Host Biosignature Identifies Tuberculosis in High and Low Endemic Countries - Chendi, Bih H.; Snyders, Candice I.; Tonby, Kristian; Jenum, Synne; Kidd, Martin; Walzl, Gerhard; Chegou, Novel N.; Dyrhol-Riise, Anne M. (Frontiers in Immunology, 2021)
Background: Several host inflammatory markers have been proposed as biomarkers for diagnosis and treatment response in Tuberculosis (TB), but few studies compare their utility in different demographic, ethnic, and TB endemic settings. Methods: Fifty-four host biomarkers were evaluated in plasma samples obtained from presumed TB cases recruited at the Oslo University Hospital in Norway, and a health center in Cape Town, South Africa. Based on clinical and laboratory assessments, participants were classified as having TB or other respiratory diseases (ORD). The concentrations of biomarkers were analyzed using the Luminex multiplex platform. Results: Out of 185 study participants from both study sites, 107 (58%) had TB, and 78 (42%) ORD. Multiple host markers showed diagnostic potential in both the Norwegian and South African cohorts, with I-309 as the most accurate single marker irrespective of geographical setting. Although study site-specific biosignatures had high accuracy for TB, a site-independent 5-marker biosignature (G-CSF+C3b/iC3b+Procalcitonin+IP-10+PDGF-BB) was identified diagnosing TB with a sensitivity of 72.7% (95% CI, 49.8 – 82.3) and specificity of 90.5% (95% CI, 69.6-98.8) irrespective of geographical site. Conclusion: a 5-marker host plasma biosignature has diagnostic potential for TB disease irrespective of TB setting and should be further explored in larger cohorts.